IMU Sensor Based Omnidirectional Robot Localization and Rotary Encoder - Marwanto, Setyo Budi; Puriyanto, Riky Dwi (Control Systems and Optimization Letters, 2023)
Localization is a technique to determine the position of the robot in an environment. Robot positioning is a basic problem when designing a mobile robot. If the robot does not know its position, then the next robot action will be difficult to determine. To be able to determine the position of the omnidirectional robot requires good speed control on the DC motor. In omnidirectional robots, positioning is through the use of a rotary encoder sensor to count the movement of the omni robot at X and Y coordinates and the IMU sensor to maintain the direction of the robot facing. PID control is also applied to control the rotational speed of each DC motor on the robot wheel. Odometry is the method used in this study. The odometry system aims to estimate the position relative to the initial position of the omni robot to estimate the change in position from time to time. The final result of this research is the application of the odometry method based on a rotary encoder and IMU sensor can produce an effective and stable robot motion and can move in all directions (holonomic) by maintaining the robot's facing direction. The results of the test form simple motions such as forward, backward, right side, and left side motion, as well as forming a box trajectory that has a position error that is not large and quite accurate. The average error value at coordinate X is 1.44 cm and at coordinate Y is 1.67 cm.